Teachers’ opinions on the education of Ukrainian refugee students (in Polish schools) - Beata Antoszewska; Urszula Bartnikowska; Monika Parchomiuk; Katarzyna Ćwirynkało; Krystian Barzykowski (Multidisciplinary Journal of School Education)
Research objectives (aims) and problem(s): The research objective was to explore Polish teachers’ opinions on the form and conditions for optimizing the educational process of refugee students from Ukraine, as well as the difficulties related to broadly understood education.